Conflict management in Kashmir : state-people relations and peace - Mahapatra, Debidatta Aurobinda (Cambridge Cambridge University Press, 2018)
The book examines the intersections of political violence, deprivation and conflict, and explores the prospects of its management by studying one of the world's most complex political turmoils - Kashmir. It closely investigates the vertical aspect of the conflict, in which the Indian state and a section of Kashmiris are engaged in a turbulent relationship, and explores ways to stimulate conflict management. By employing the protracted social conflict theory, the author argues that a conflict between a state and a social group ensues when the political elite fail to address the non-material needs of the marginalized. By documenting narratives of the Kashmiri traders and the state officials, and the impact of the opening of the two intra-Kashmir trade routes during the 1990s, this book emphasizes the need to focus on peace initiatives taken by the government, and the significance of accommodation and engagement to address a state-people conflict.
Includes bibliographical references and index.
Keywords: Peace-building; Conflict management